Effects of 2,4-D, glyphosate and paraquat on growth, photosynthesis and chlorophyll–a synthesis of Scenedesmus quadricauda Berb 614 - Wong, P.K. (Chemosphere (Oxford), 2000)
The effects of 2,4-D, glyphosate and paraquat on growth, photosynthesis and chlorophyll- a synthesis by a freshwater green alga, Scenedesmus quadricauda Berb 614, were determined. These herbicides are the most often used in Hong Kong. Within the concentration range 0.02–200 mg/l, paraquat was more toxic than glyphosate and 2,4-D to the growth, photosynthesis and chlorophyll- a synthesis. The presence of 0.02, 0.2 or 2 mg/l of 2,4-D was not toxic to the alga. Algal growth, photosynthesis and chlorophyll- a synthesis were stimulated by the presence of low concentrations (0.02 or 0.2 and 0.02 mg/l, respectively) of 2,4-D and glyphosate. The presence of 0.02 or 0.2 mg/l of paraquat, 2 mg/l of glyphosate or 20 mg/l of 2,4-D was significantly inhibitory to the three test parameters, whereas the presence of 2 or more mg/l of paraquat, 20 or more mg/l of glyphosate or 200 mg/l of 2,4-D completely inhibited algal growth, photosynthesis and chlorophyll- a synthesis. The use of the alga as a bio-indicator of herbicide contamination in freshwater environment was discussed.